Workshop Pengelolaan Media Pembelajaran Berbasis Loose Parts - Irony Damianus Saefatu; Maryance Ferawati Tamelab; Retno K.Lopo; Engelbertus Seran; Margaretha Hege Udju; Rizky Brilyanti Mauwalan (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2025)
This Community Service activity aimed to enhance early childhood education (ECE) teachers’ understanding and skills in managing Loose Parts-based learning media in Mollo Selatan Subdistrict, Timor Tengah Selatan Regency. The methods involved workshops and intensive mentoring with 42 participants. The results demonstrated improved understanding and skills in integrating Loose Parts into the Merdeka Curriculum, positively impacting children's creativity and learning experiences. This program is expected to provide sustainable solutions for ECE learning innovations.